Urinary 6-sulfatoxymelatonin level in girls and its relationship with obesity - Jieun Lee; Juyoung Yoon; Jin A Lee; Seong Yong Lee; Choong Ho Shin; Sei Won Yang (Korean Pediatric Society, 2012)
PurposeShort sleep duration is associated with obesity. Urinary 6-sulfatoxymelatonin (6-OHMS), the principal metabolite of melatonin, is closely related with sleep. We evaluated the difference in urinary 6-OHMS levels between obese girls and normal weight girls, and the relationship of urinary 6-OHMS with other hormones regulating body weight and metabolism.MethodsA total of 79 girls (6.3 to 12.4 years) were included in this study, of whom 34 were obese; 15, overweight; and 30, normal-weight. We examined their pubertal status and bone age. Fasting serum levels of total ghrelin, leptin, insulin, and first morning urinary 6-OHMS were measured. Homeostatic model assessment-insulin resistance (HOMA-IR) was calculated from the fasting insulin and glucose levels.ResultsThere was no significant difference in the creatinine adjusted 6-OHMS levels between the obese girls and the control group. Urinary 6-OHMS did not show any correlations with body mass index (BMI), BMI percentile, total ghrelin, leptin, and HOMA-IR. Negative correlations were found between urinary 6-OHMS levels and chronological and bone ages.ConclusionOur results suggest that melatonin production is not reduced consistently in obese girls.